Towards developing and validating Quality Physical Education in schools—The Asian physical education professionals’ voice - van Wouwe, Jacobus P.; Ho, Walter King Yan; Ahmed, Md. Dilsad; Khoo, Selina; Tan, Chee Hian; Dehkordi, Mitra Rouhi; Gallardo, Mila; Lee, Kicheon; Yamaguchi, Yasuo; Tao, Yuping; Shu, Chunong (Public Library of Science, 2019)
Physical education professionals aim to develop quality programmes for physical education. This study aimed to develop and validate a scale using professionals’ perceptions of Quality Physical Education QPE in Asia using twenty-four items regarding QPE quality issues. The items covered status and roles, development of educational elements and supportive features in physical education. A sample of N = 799 sport and physical education professionals from eleven Asian cities participated in this questionnaire survey. Twenty-four items relating to QPE were examined via exploratory factor analysis (EFA) using maximum likelihood extraction and direct oblimin rotation methods. Nevertheless, only 20 items were extracted following the EFA examination. Items 1, 9, 14 and 18 were excluded because of low factor loadings. The remaining items were clustered into four subscales: Development and Supportive Elements for Quality Physical Education in Schools (DSFQPE; α = .918), Core Values of Quality Physical Education (CVPE; α = .908), Curriculum Arrangement of Physical Activities (CAPA; α = .884) and Provision and Norms in Physical Education (PNPE; α = .865). The Cronbach’s alpha coefficient (α = .875) indicated excellent internal consistency for the overall measure. Furthermore, the 4 retained factors from the EFA were assessed via robust confirmatory factor analysis (CFA). The 4-factor model demonstrated a good fit with the data (CMIN/DF = 3.450, CFI = .928, TLI = .916, PCFI = .801, RMSEA = .078). The study identified a 4-factor structure with internal consistency and acceptable interfactor correlations. The structure seemed to be applicable, including the twenty items identified as useful and necessary tools for the framework of analysis in the investigation of diverse settings for the study of quality physical education. © 2019 Ho et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.